Analisis Kepatuhan Ibu Terhadap Pemberian Imunisasi DPT Pada Balita Di Puskesmas Bandar Jaya Kabupaten Lahat - Salmastuti Salmastuti (Jurnal Kesehatan Saelmakers PERDANA, 2022)
The most important Pusekesmas Program is the Maternal and Child Health (KIA) Program. Basic immunization in the form of DPT immunization is one of the programs carried out by the Puskesmas in the Maternal and Child Health (KIA) Program. Indonesia is one of the countries with a large number of children who do not get complete immunization. Data on complete basic immunization coverage at Bandar Jaya Health Center is 93,5 %, while the target for complete basic immunization coverage is 95 %. There is a decrease in data on DPT Imunization visits for toddlers at the Bandar Jaya Health Center, Lahat Regency in 2020. Research purposes : to determine the Analysis of Maternal Compliance (Knowledge, Education, Profession, Attitude, and Family Support) in providing DPT Immunization to Toddlers in the work area of the Bandar Jaya District Health Center Lahat in 2021. The research method : uses a cross sectional study design, this research was conducted from June 30 to July 23, 2021 with a purposive sampling technique. The sample in this study were mother who visited to provide DPT Immunization to their toddlers, totalling 65 people. Data were taken by questionnaire and anlyzed by Univariate Analysis, Bivariate by Chi-square test and Multivariate Analysis by Multiple Logistic Regression. The results showed that there was a relationship between mothers education and P-value (0,05). And there is no relationshio between mother’s knowledge and her P-value (0,19), there is no relationship between mother’s work and her P-value (0,15), there is no relationship between mother’s attitude and her P-value (0,56) and there is no relationship on support mother;s family with his P-value (0,12). The dominant variable is education with a ? value (1,78) and P-value (0,01). In conclusion, there is a relationship between mother’s education and compliance with DPT immunization in toddlers and there is no relationship between knowledge, work, attitudes and family support with adherence to DPT immunization on toddlers. It is recommended for the Bandar Jaya Public Health Center to conduct socialization and counseling both directly and by distributing leaflets about the importance of DPT Immunization for toddlers so that mothers of toddlers can obtain optimal knowledge about DPT Immunization.